Self-Reported Sexually Transmitted Disease–Related Health Services Among Men Who Have Sex With Men in the United States, 2011 to 2017. Issue 3 (March 2020) - Haderxhanaj, Laura T.; Leichliter, Jami S.; Dittus, Patricia J.; Spicknall, Ian H.; Aral, Sevgi O.
Abstract : Abstract: From a nationally representative survey, 2011 to 2017, we found that 80.7% of sexually active men who have sex with men were insured and 82.0% had a usual place for care, but only 39.8% received sexual risk assessment and 45.8% received sexually transmitted disease screening, of whom 58.0% received extragenital sexually transmitted disease screening. Abstract : In the United States, sexually active men who have sex with men receive sexual risk assessments and sexually transmitted disease screening at frequencies below national recommendations. Extragenital screening is especially infrequent.